Legal Protection for Housing Developers under Protected Rice Field Policy - Nolanda Fadiahaya Trigosa; Herlindah; Indah Dwi Qurbani (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This research examines the legal implications arising from the unilateral conversion of land ownership status into Protected Rice Fields (Lahan Sawah Dilindungi or LSD) in Madiun Regency following the issuance of the Decree of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (Decree of the Minister of ATR/BPN) Number 1589/SK-HK.02.01/XII/2021 of 2021. The designation creates legal uncertainty for housing developers who had previously obtained legal land rights based on Regional Regulation Number 9 of 2011 concerning the Spatial Plan of Madiun Regency for 2009–2029. The absence of synchronization between the LSD policy and the Regional Spatial Plan (RTRW) generates normative inconsistencies, resulting in legal and economic losses for developers. This study, therefore, seeks to analyze the legal status of the LSD designation and the forms of legal protection available for affected developers. Using a normative juridical method with statute, conceptual, and case approaches, the research analyzes primary, secondary, and tertiary legal materials through descriptive-analytical techniques employing grammatical and systematic interpretation. The findings show that the legal position of the Ministerial Decree is problematic in both authority and hierarchy. Although the Ministry of ATR/BPN possesses attributive authority to establish LSD, implementing such designation without harmonization with regional spatial planning constitutes an overextension of authority and ignores decentralization principles. As a result, the decree holds weak normative force and should be considered an administrative policy requiring alignment with regional regulations. Furthermore, legal protection for developers may be provided preventively through regulatory harmonization between RTRW and LSD policies, and repressively through administrative remedies or judicial review before the Administrative Court (PTUN), including claims based on on-rechtmatige overheidsdaad.